The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/fsn3.2448
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest melatonin treatment inhibited longan (Dimocarpuslongan Lour.) pericarp browning by increasing ROS scavenging ability and protecting cytomembrane integrity

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
(113 reference statements)
1
14
0
Order By: Relevance
“…The increase in ion leakage in CI-damaged fruit is due to an increased action of membrane lipid-degrading enzymes, leading to reductions in the concentration of unsaturated fatty acids and the unsaturated:saturated fatty acid ratio, increased cell membrane permeability and disruption of the compartmentalised function of the cell membranes [ 30 , 31 , 32 ]. Similar to the present results, melatonin postharvest treatments have been shown to increase chilling tolerance in several fruit species, such as litchi [ 31 ], pepper [ 32 ], guava [ 33 ], peach [ 34 ], longan [ 35 ] and banana fruit [ 36 ]. This effect has been attributed to the maintenance of cell membrane structure and permeability, due to a higher content of unsaturated fatty acids and enhanced antioxidant enzyme activities, which lead to lowering the accumulation of malondialdehyde (MDA) and reactive oxygen species (ROS) and maintaining the cellular redox state.…”
Section: Discussionsupporting
confidence: 89%
“…The increase in ion leakage in CI-damaged fruit is due to an increased action of membrane lipid-degrading enzymes, leading to reductions in the concentration of unsaturated fatty acids and the unsaturated:saturated fatty acid ratio, increased cell membrane permeability and disruption of the compartmentalised function of the cell membranes [ 30 , 31 , 32 ]. Similar to the present results, melatonin postharvest treatments have been shown to increase chilling tolerance in several fruit species, such as litchi [ 31 ], pepper [ 32 ], guava [ 33 ], peach [ 34 ], longan [ 35 ] and banana fruit [ 36 ]. This effect has been attributed to the maintenance of cell membrane structure and permeability, due to a higher content of unsaturated fatty acids and enhanced antioxidant enzyme activities, which lead to lowering the accumulation of malondialdehyde (MDA) and reactive oxygen species (ROS) and maintaining the cellular redox state.…”
Section: Discussionsupporting
confidence: 89%
“…However, the quality deterioration of longan fruit occurs rapidly within a few days under normal temperature storage, mainly manifested as pericarp browning, aril breakdown and decay. The physiological basis of pericarp browning and aril breakdown of longan fruit has been studied extensively in the past few decades [ 3 ]. Postharvest pericarp browning of longan fruit was believed to be caused by the oxidation of phenolics by peroxidase (POD), polyphenol oxidase (PPO) [ 4 ] and the recently reported Laccase 14-4 [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, delayed declines in total phenolics, flavonoids, and anthocyanins corresponding to suppressed enhancements in the activities of PPO and POD were observed in MT-treated rambutans during storage, implying that MT could confer protection against subcellular decompartmentalization and contribute to the amelioration of enzymatic browning. Consistent control of phenolic oxidation associated with improved postharvest quality in response to MT was noted in litchis ( 18 ), pears ( 48 ), longans ( 22 ), and bananas ( 49 ).…”
Section: Discussionmentioning
confidence: 65%
“…The results demonstrated that MT at an optimum concentration (0.125 mmol L –1 ) markedly slowed down the advancement of pericarp browning and discoloration, as manifested by the lower browning index and higher chromaticity L *, a *, and b * values in MT-treated fruit compared with those in untreated fruit. Comparable prevention against browning and color loss achieved by postharvest application of MT also occurred in other Sapindaceae fruits, such as litchis ( 18 , 35 ) and longans ( 22 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation